An analysis of the suitability of selected newspaper material as a teaching resource in efl courses - Cruz, Gladys (2010)
The research about “ An analysis on the suitability of selected newspaper material as a teaching resource in EFL courses”, showed that newspapers are interesting resources for using them as didactic material for teaching English as a second language, specially with the variable reading.Reading has many purposes. We can read for pleasure or entertainment, looking information , for learning, and so on, depending on what we want from the text; taking into account the reader’s interest, motivation and the way in which he/ she reads, or the place where the reading is done.